Morphological Change of Dhaka City Over a Period of 55 Years: A Case Study of Two Wards (Journal of Bangladesh Institute of Planners, 2024)
Dhaka City has undergone radical changes in its physical form, not only by territorial expansion, but also through internal physical transformations over the last decades. These have created entirely new kinds of fabric. With these changes, the elements of urban form have changed. Plots and open spaces have been transformed into building areas, open squares into car parks, low land and water bodies into reclaimed built-up lands etc. This research has its general interest in the morphologic change of Dhaka City. It focuses on the spatial dynamics of urban growth of Dhaka over the last 55 years from 1952-2007. In the research, the transformation of urban form has been examined through space syntax. The aim behind using this technique is to describe aspects of relationships between the morphological structure of man-made environments and social structures and events. To conduct this research, Wards 49 and 72 of Dhaka City Corporation were selected as the study areas, of which Ward 72 is an indigenous and Ward 49 is a planned type of settlement. Being a planned residential area, the syntactic measures from this morphological analysis are showing quite unchanged and high values in all phases for Ward 49 and the physical characteristics of Ward 72 (Old Dhaka) still represent the past. The syntactic values are found to be higher for Ward 72 and than Ward 49. Higher values indicate that the street network is highly connective among each other. Time affects differently the layout of cities and the architecture of buildings. Of the many human creations, street systems are among the most resistant to change. This has been emphasized in this study, thereby facilitating the comparison of urban layouts across space and time. The interpretation of history in the light of quantitative accounts, as demonstrated in this study, will be of value to urban planners and urban designers for the future planning of modern Dhaka City.DOI: http://dx.doi.org/10.3329/jbip.v2i0.9554  Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 30-38